Kajian Terhadap Review Desain Jembatan Way Panas, Desa Margomulyo – Lematang, Kecamatan Jati Agug, Lampung - I Wayan Diana; Hadi Ali; Ketut Swandana (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2016)
This design is done to determine the level of efficiency the most economical to aligment and geom- etry of bridge have been built. As long as gain alternative type of structure on bridge which should used in way panas. Calculations in this design cover the building upon and under constuction the bridge. With calculations result of dead load and live load, followed bye look for to moment force and normal force. Until found of dimension and reinforcement needed for each building. And next calculations of estimated engineering use RAB. Based on the result of design it is concluded geometry changes of bridge from the span 12 to 16 meter provide curve geometry is better then position the existing. Bridge reinforcement analysis with ultimate analysis give efficiency reinforcement to 806,69 kg be compared with standard BM- 100 with flexible analysis. On implementation with BM-100 result the reinforcement of 3876,3 kg. The cost implementation with unit price of material (RAB) is IDR 975.000.000,- under own estimate.